2007
DOI: 10.1002/cncr.22443
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of adiposity and weight change in relation to prostate cancer incidence and mortality

Abstract: The crystalline structure of the heat‐sealed part of oriented polypropylene (OPP) and cast polypropylene (CPP) films was investigated by differential scanning calorimetry, Fourier transform infrared spectroscopy, and thermal mechanical analysis (TMA). The relationship between the crystalline structure and the mechanical properties was analyzed. It was found that the high total crystallinity of both OPP and CPP gave rise to good mechanical properties and that the orientation of the crystalline structure in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
258
8
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(296 citation statements)
references
References 53 publications
(73 reference statements)
20
258
8
4
Order By: Relevance
“…3,[5][6][7][8][9] Previous studies also found an association between weight loss and decreased risk of developing high-grade PC, and an association between weight gain and BCR risk and PC mortality, 3,4,10 though in these studies, weight change was evaluated over many years. One study found perioperative weight gain is associated with increased recurrence vs men with stable weights.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,[5][6][7][8][9] Previous studies also found an association between weight loss and decreased risk of developing high-grade PC, and an association between weight gain and BCR risk and PC mortality, 3,4,10 though in these studies, weight change was evaluated over many years. One study found perioperative weight gain is associated with increased recurrence vs men with stable weights.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Among men with PC, obesity is linked with high-grade disease and biochemical recurrence (BCR) after radical prostatectomy (RP). 3,[5][6][7][8][9] Given obesity is a condition of excess body weight, it is unclear whether the obese state itself or the energy imbalance required to become obese is responsible for the poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Furthermore, clinical prostate cancer risk has been associated with the metabolic syndrome, 13,14 centralized obesity, 15 leptin levels [16][17][18] and insulin resistance. 19,20 However, several studies report no evidence of an association, [21][22][23][24][25][26][27] while others report that BMI is associated with reduced risk of prostate cancer, particularly low-grade tumors. [28][29][30] Finally, there is evidence that prostate cancer risk changes with time following a diabetes diagnosis, from an increased risk proximal to the diabetes diagnosis to a reduction in risk, 31,32 perhaps related to diabetes treatment, disease progression or changes in prostate cancer screening practices with time following a diabetes diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 It has therefore been suggested that obese men experience a detection bias, minimising or even reversing the association between obesity and PCa risk (i.e., obesity becomes 'protective'), as demonstrated by several recent large prospective cohort studies. [18][19][20] However, we hypothesize that the association between obesity and advanced disease will persist if obesity is biologically linked with aggressive disease. 21 Indeed, a meta-analysis of multiple prospective Obesity-related lowered PSA on PCa screening WJ Yang 771 studies found that although obesity has a null or slightly protective effect in localized disease, it is associated with an increased incidence of advanced PCa.…”
Section: Discussionmentioning
confidence: 97%